Impact and Sustainability of a 10-year Community Pharmacy Disease Management Service - Tammy Lopez; Wesley Nuffer (University of Minnesota Libraries Publishing, 2021)
Background. Community pharmacy practice needs to demonstrate services beyond traditional dispensing roles to continue to function in a changing marketplace. Pharmacists have established themselves as being capable of improving patient outcomes and saving healthcare dollars by providing disease management services to patients. This paper describes a sustained community pharmacy-run disease management program that continued after a grassroots grant-funding effort in 2007. Methods. The city of Colorado Springs recognized the successes shown by the pharmacy during the Ten City Challenge funded project, and decided to financially support pharmacy diabetes care services. Partnering with the local School of Pharmacy, the pharmacist obtained advanced training and continued to deliver individualized counseling and management to approximately 100 patients per year for the past 14 years. Objective lab measurements (systolic and diastolic blood pressures, A1C values, total lipid profiles) were obtained or performed, and clinical goals were set based on national guidelines. Patients received a series of appointments to learn how to control their diabetes, and later their cardiovascular disease. Financial estimates were calculated using 2008 baseline numbers and adding estimated inflation based on published Segal rates. Results. The pharmacy services successfully maintained participation of approximately 100 patients annually each year since its inception. Average lab value markers for disease control were at or close to clinical guideline recommendations for the population. Services were associated with estimated cost savings for the health system. Positive results led to expansion in services to include cardiovascular disease in 2017. Conclusions. A community pharmacy has successfully sustained a disease management program for patients for over 14 years, demonstrating high patient enrollment, health outcomes at or near clinical guidelines for control, and positive financial outcomes associated with the program.